The Optical and Spectroscopic Properties of Fuchsite, Spodumene, and Lepidolite from Northern Scandinavia (Kautokeino, Kaustinen, Kolmozero) - Miłosz Huber; Daniel M. Kamiński; Urszula Maciołek (Materials, 2023)
Li-Ce-Ta (LCT) pegmatites containing lithium mineralization in the form of spodumene and lepidolite, as well as fuchsite, from the regions of northern Scandinavia (N Norway, N Finland, N Russia) were studied. Detailed analyses of the chemical compositions of these minerals were carried out, involving scanning electron microscopy (SEM) with energy-dispersive spectroscopy (EDS), Fourier transform infrared (FTIR) spectroscopy with attenuated total reflectance (ATR), and X-ray photoelectron spectroscopy (XPS) studies. Their crystal structures were confirmed with the X-ray diffraction technique. Studies involving microscopy were also carried out, indicating the optical features of these minerals. Based on the analyses carried out in the studied rocks, the characteristics of these minerals were determined, as well as the crystallization conditions. This research indicates that the N Scandinavian area is prospective and may lead to further discoveries of this type of pegmatite in the studied region.